AB1128 ULTRASOUND SYNOVITIS AND SQUEEZE TEST: IS THERE A RELATIONSHIP?. (13th June 2020) - Ben Abdelghani, K.; Saadaoui, K.; Fazaa, A.; Miladi, S.; Ouenniche, K.; Souabni, L.; Kassab, S.; Chkili, S.; Zakraoui, L.; Laatar, A.
Abstract : Background: The squeeze test or the Gaenslen's test is an easy and rapid method to identify arthritis in metacarpophalangeal (MCP) and metatarsophalangeal (MTP) joints. It's characterized by tenderness upon lateral compression of MCP or MTP joints. This is a useful clinical exam for the early diagnosis of Rheumatoid Arthritis (RA). Objectives: The aim of our study is to assess the real value of that test and its association with synovitis. Methods: A prospective study including RA patients (2010 ACR/EULAR criteria) was conducted at the Rheumatology Department of Mongi Slim Hospital Tunis. US examination was performed by an experimented rheumatologist blinded to clinical data using a machine type Esaote MyLAb 60 with a linear probe of 6-18 MHz. MCP joints were assessed in dorsal longitudinal view, in mode B and Power Doppler. Synovitis was defined and Flexor digitorum Tenosynovitis was defined according to OMERACT. A p<0.05 was considered statistically significant. Results: Forty-three cases of RA were included. The mean age was 58.92 years [27 - 81]. The sex ratio was 0.16. Among our patients, 46.5% of cases were receiving methotrexate with a mean dose of 15, 875 mg / week [7.5 - 22.5]. Corticosteroids were used in 55.8% of our patients with a mean dose of 8.65 mg / day [2.5 - 30]. Moreover, 23.25% of the patients were on biologics. The mean value of morning stiffness was 37 min [0 - 150], the mean value of the global assessment of the disease by the patient was 5/10 [1 - 8]. The Gaenslen's test was positive bilaterally in 25, 6% of cases, in the right hand and in the left one in respectively 39.5% and 27.9% of the patients. Tenosynovitis of the flexors were found clinically in 11.6% case. The mean CRP was 29.7 mg / L [0.2 - 275] and the mean ESR was 65 mm [3 - 120]. The mean value of DAS28 and DAS28 CRP were respectively 5.20 ± 1.43 [2.69 – 9.00] and 4.33 ± 1.43 [1.35 – 8.32]. Overall, 430 joints and 430 flexor tendons were assessed by Ultrasound. Ninety-one synovitis were detected with a mean of 2.56 synovitis in MCP per patient [0 - 10]. Flexor tenosynovitis was found in 53.5% of patients. A statistically significant correlation was found between the squeeze test and presence of ultrasound synovitis of the MCP whatever the site of the synovitis; on the right side (r = 0.507; p < 10 -3 ), or the left one (r = 0.607; p < 10 -3 ) but no correlation between the clinically detected tenosynovitis and the ultrasound tenosynovitis (p = 0.364). We found a significant correlation between the Gleason test and ultrasound tenosynovitis on both side with r = 0.368 and p = 0.015 on the right hand and r = 0.441 and p = 0.003 on the left one. Conclusion: The squeeze test seems to be a very useful and practical clinical examination to easily detect synovitis and aid in the early diagnosis of RA Disclosure of Interests: None declared